Biochemical Effect of Aqueous Leaf Extract of Detarium microcarpum in Wistar Rats - Ahmed, Maryam Usman; Isreal, Domasun; Titus, Diowato; Ayinla, Abdulfatai Abayomi; Aliyu, Kamaludden; Etuk, Idongesit (African Journal of Clinical Medicine and Pharmacy Research, 2025)
Herbal remedies have been used since ancient times, often sourced from local traditional healers. However, many of these preparations are administered without thorough scientific evaluation. This study aimed to assess the effects of aqueous leaf extract of Detarium microcarpum on liver and kidney function in Wistar rats. A total of 25 male rats were randomly assigned to five groups of five animals each. Groups 2, 3, 4, and 5 received oral doses of 200, 400, 600, and 800 mg/kg body weight of the extract, respectively, for 21 consecutive days. Group 1, serving as the control, received only normal saline. Liver function was evaluated by measuring serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), total protein, and albumin. All liver parameters exhibited a significant dose-dependent increase (p<0.05) in the treatment groups compared to the control, indicating hepatotoxic effects. Similarly, kidney function parameters, including bicarbonate (HCO₃⁻), chloride (Cl⁻), sodium (Na⁺), and potassium (K⁺), also showed a significant dose-dependent increase. Conversely, levels of urea and creatinine significantly decreased (p<0.05) in the extract-treated groups relative to the control. The findings suggest that the aqueous leaf extract of D. microcarpum adversely affects liver and kidney function in a dose-dependent manner. Therefore, despite its traditional use, the extract should be considered potentially toxic and used with caution.